The Effect Of Product Innovation And Business Competition On The Development Of MSMES In Harjosari I Substance, Medan Amplas - Apriyani Hizriah Hsb (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
This study analyzes the effect of product innovation and business competition simultaneously on the development of MSMEs in Harjosari I Village, Medan Amplas District. The population in this study were all MSMEs in Harjosari I Medan Amplas Village as many as 62 MSMEs. Saturated sampling technique is a sampling technique when all members of the population are used as samples. Since the number of MSMEs in Harjosari I Medan Amplas Village is 62 MSMEs (less than 100 people), all MSMEs are taken as objects of research. The place of this research was conducted on Jl. Sisingamangaraja, Jl. Garu I to Garu VIII, Harjosari I Village, Medan Sandpaper. The time of this research starts in October 2021 until March 2022. The research method used in this study is the method of observation, documentation and questionnaires using a Likert scale. The analytical method used is the multiple linear regression method using the SPSS program. The results of the research with a partial test that Product Innovation has a t value of 4.714 > 1.6698, so it can be concluded that the Product Innovation variable has a positive and significant impact on the development of MSMEs in Harjosari I Village, Medan Amplas District. Business Competition has a t-count value of 3.704 > 1.6698, so it can be concluded that Business Competition has a positive and significant effect on the development of MSMEs in Harjosari I Village, Medan Amplas District. Based on the results of the F test (simultaneous) that jointly Product Innovation and Business Competition have a positive and significant impact on the development of MSMEs in Harjosari I Village, Medan Amplas District with a value of F count > F Table (41.430 > 3.15). The results of the analysis of the coefficient of determination (R2) indicate that Product Innovation and Business Competition have an influence on the development of MSMEs in Harjosari I Village, Medan Amplas District with a value of 58.4%, while the remaining 41.6% is influenced by other variables not examined in the study. this